Pretreatment total lymphocyte count as a prognostic factor of survival in patients with recurrent cervical cancer after definitive radiation-based therapy: a retrospective study - Ekasak Thiangphak; Kittinun Leetanaporn; Rakchai Buhachat (Korean Society of Obstetrics and Gynecology, 2023)
Objective This study evaluated the association between pretreatment total lymphocyte count (TLC) and overall survival (OS) in patients with recurrent cervical cancer. Methods We retrospectively reviewed 290 patients with recurrent cervical cancer with definite complete responses to either definitive radiotherapy or concurrent chemoradiotherapy between January 2009 and December 2022. The associations between pretreatment TLC and progression-free survival (PFS) and OS rates were evaluated. Results Ninety-three patients (32%) had a pretreatment TLC <1,000 cells/mm3. Patients with a pretreatment TLC <1,000 cells/mm3 had lower treatment response rates than their counterparts (P=0.045). The OS and PFS rates were significantly higher in patients with pretreatment TLC ≥1,000 cells/mm3 than in those with pretreatment TLC <1,000 cells/mm3 (10.74 vs. 3.89 months, P<0.0001; 8.32 vs. 4.97 months, P=0.042; respectively). Moreover, pretreatment TLC ≥1,000 cells/mm3 was identified as an independent prognostic factor for OS in both univariate analysis (hazard ratio [HR], 0.57; 95% conficence interval [CI], 0.44-0.74; P<0.001) and multivariate analysis (HR, 0.64; 95% CI, 0.47-0.86; P=0.003). However, TLC ≥1,000 cells/mm3 was identified as a prognostic factor for PFS only in univariate analysis (HR, 0.71; 95% CI, 0.51-0.99; P=0.043) but not in the multivariate analysis (HR, 0.81; 95% CI, 0.55-1.18; P=0.3). Conclusion Pretreatment TLC was associated with treatment response and was identified as an independent prognostic factor associated with the survival outcomes of patients with recurrent cervical cancer.